CO2 Sequestration
The method of hydrothermal treatment and dehydration of ultramafic rocks efficiently captures CO2, addressing inefficiencies in existing olivine-based sequestration methods by producing a binder for concrete applications.
Patent Information
- Application Number
- JP2024541794
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-01-12
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-01-12
AI Technical Summary
Existing methods for carbon dioxide sequestration using olivine are inefficient and require high energy input, complex technology, and expensive materials, with limited conversion rates and scalability issues, while natural application methods fail to capture significant atmospheric CO2.
A method involving hydrothermal treatment and dehydration of ultramafic rocks or industrial wastes with high MgO content, followed by reactive milling and controlled exposure to CO2, to produce magnesium carbonate for efficient CO2 binding.
Achieves high CO2 capture rates with low energy input, producing a binder suitable for concrete production, capable of binding CO2 efficiently and cost-effectively.
Smart Images

Figure 2025501392000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for sequestration of CO2. [Background technology]
[0002] Carbon dioxide (CO2) acts as a greenhouse gas in the atmosphere and is considered one of the main causes of anthropogenic global warming. In addition to radically reducing CO2 emissions, parallel efforts are being made to bind the CO2 already present in the atmosphere. By binding CO2, manufacturing processes that emit large amounts of CO2, such as cement production, can also be made CO2-neutral.
[0003] CO2 sequestration specifically refers to removing CO2 from the atmosphere, ideally by binding it with other substances so that it is not released again. Various proposals for this are known. One possibility is to use olivine.
[0004] Olivine is a mineral with a general composition A2[SiO4], where A can be a mixture of various divalent ions such as magnesium (forsterite, Mg2SiO4), iron (Fe2SiO4, fayalite), and manganese (Mn2SiO4, tefloite), as well as other ions and combinations of various cations; olivine is a solid solution series.
[0005] The patent literature on accelerating carbon dioxide sequestration by reaction with olivine is very extensive. Many methods for sequestrating carbon dioxide using olivine are based on the following principles and differ mainly in the way the reaction is accelerated:
[0006] [ka]
[0007] According to WO 2007 / 069902, the reaction should be accelerated by grinding and adjusting a certain pH value, and WO 2008 / 140821 and WO 2008 / 061305 suggest that the reaction is accelerated by high temperature, high CO2 partial pressure, and high fineness of olivine. WO 2008 / 101293 suggests the addition of ammonium, WO 2007 / 106883 suggests the addition of a base, and US 4944928 suggests the addition of hydrochloric acid.
[0008] In addition to these methods, there are many other methods that can accelerate the sequestration of carbon dioxide during reaction with olivine, but all these processes use complex technologies and expensive starting materials.
[0009] The CO2min project attempts to combine such olivine carbonation with cement production. The aim is to separate CO2 emissions from the cement industry by carbonating olivine. As a result, cement production continues unchanged while maintaining the existing high-temperature process. The resulting carbon dioxide is combined with olivine in the form of magnesium carbonate and SiO2 by reaction. This generated material is then added to the cement and disposed of. However, it is obviously not possible to convert olivine completely into magnesium carbonate (see D. Kremer, H. Wotruba, "Separation of products from mineral sequestration of CO2 with primary and secondary materials", Minerals, Vol. 10 (2020), pp. 1098 ff.). In this project, very high CO2 partial pressures (17 bar) and high temperatures (175 °C) were used. Despite autoclaving, the conversion rate of olivine is only 23%, and very large quantities of olivine are required to compensate for the low conversion rate. The process technology chosen is also probably not suitable for carbon dioxide binding on an industrial scale.
[0010] Another idea of binding carbon dioxide through reaction with olivine has also been developed in the Netherlands (see R.D. Schuiling, P. Krijgsman, "Enhanced Weathering: An effective and cheap tool to sequeter CO2", Climate Change, Vol. 74 (2006), pp. 349-354). Olivine is then spread on arable land or spread on coasts. When olivine is dissolved in magnesium ions, rainwater or seawater reacts with HCO3 according to the following equation: - Carbon dioxide can be simultaneously absorbed in the form of ions.
[0011] [ka]
[0012] However, laboratory experiments at the University of Hamburg have shown that the described reactions do not occur in the described way: even if olivine were spread over the entire arable land of the world, it would only capture 0.2% of the world's carbon dioxide emissions (see T. Amann et al., "Enhanced weathering and related element fluxes- a cropland mesocosm approach," Biogeosciences, Vol. 17 (2020), pp. 103-109). Summary of the Invention [Problem to be solved by the invention]
[0013] It is therefore an object of the present invention to provide an efficient method for sequestering CO2. [Means for solving the problem]
[0014] According to the invention, this object is achieved by a method having the features of claim 1.
[0015] Further advantageous embodiments are defined in the dependent claims, further descriptions and exemplary embodiments. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a graph showing the hydration process of the product produced by the method of the present invention. [Diagram 2] FIG. 2 is a graph showing the curve of CO2 concentration during the binding of CO2 by the product produced using the method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] According to claim 1, firstly a starting product is provided which comprises at least 20% by weight, preferably at least 40% by weight, more preferably at least 60% by weight, even more preferably at least 80% by weight of one or more of the following components: These components may be ultramafic rocks such as dunite, serpentinite, weathering products of ultramafic rocks such as olivine, or industrial waste. It is essential that all of these raw materials have an MgO concentration or MgO content of at least 10% by weight, preferably 20% by weight, even more preferably 30% by weight or more, ideally 40% by weight or more. This starting product is preferably 0.1 m 2 The fineness corresponds to a BET surface area of at least 0.5 m / g. 2 / g is advantageous, and 1.0m 2 / g or more is even more preferred.
[0018] The important mineral of ultramafic rocks is olivine, a mixed crystal series of fayalite (Fe2SiO4), forsterite (Mg2SiO4), tefloite (Mn2SiO4) and other minerals of the A2[SiO4] type. Natural olivine deposits have been documented, and olivine is often an iron-bearing, magnesium-rich material. Examples of industrial waste that can be used in the present invention include foundry sand and refractories.
[0019] When the starting product is provided, the starting product is homogenized if necessary.The possible components of the starting product mentioned above are often materials from natural rocks or natural deposits.Experience shows that they are not available in pure form and are not homogenized.Homogenization can be carried out, for example, using a mixer or simultaneously with grinding to the desired fineness.
[0020] Following homogenization, the starting product thus prepared is hydrothermally treated. This treatment is carried out in a heat treatment device at a temperature above 100° C. for at least 24 hours. The heat treatment device is a heat tunnel, but can also be, for example, an autoclave. An autoclave is generally understood to be an airtight, sealable pressure vessel that can be used for the heat treatment of substances in the overpressure range. A heat treatment device is preferably understood as a vessel, a combination of devices such as ovens and closed types, or a device that confines a volume. The treatment is preferably carried out at a temperature of 100° C. or higher, in particular 150° C. or higher, more preferably 250° C. or higher. Also, good conversion is obtained if the treatment is carried out for 36 hours or more, more preferably 48 hours or more. However, particularly good results are obtained by carrying out the treatment for a longer period, for example for several days, for example 4 days, more preferably 7 days or more.
[0021] Additionally, water may be added to the homogenized starting product by adding water immediately prior to, after, and / or simultaneously with homogenization in a previous step and mixing the water with the starting product. Alternatively or additionally, steam may be introduced into the heat treatment device.
[0022] During the hydrothermal treatment of the homogenized starting product, the presence of HO at least partially converts it into magnesium hydroxide (Mg(OH)2) and magnesium silicate hydrate (Mg3Si2O5(OH)4, Mg3Si4O 10 (OH)2). The basic reaction here is, shown here in a simplified form starting with forsterite (Mg2SiO4):
[0023] [ka]
[0024] Here, reaction (1) mainly occurs. This is also preferred in the present invention because Mg3Si2O5(OH)4 is 10 It should also be noted that the amount of each product and their ratios depend, among other things, on the exact composition of the starting products.
[0025] Magnesium hydroxide (Mg(OH)2) can occur as brucite. Magnesium silicate hydrate (Mg3Si2O5(OH)4, Mg3Si4O 10 (OH)2) exists in the form of lizardite, antigorite, talc, etc. It is noteworthy here that the stoichiometric water content of antigorite is sometimes lower (13% by weight) than the range of 16% to 20% by weight that can be measured by testing. This can be explained by the fact that some materials are so fine that water can adhere to the surface.
[0026] Similarly, such deviations from stoichiometry apply to the ratio of Mg to Si. Furthermore, foreign ions such as Fe may also be incorporated in the reaction products. However, other reaction products such as hydromagnesite, hematite, magnetite, gibbsite, etc. may also be produced. This depends in each case on the exact composition of the starting products. All or part of the reaction products may contain iron, carbonate, alkali, or other foreign ions.
[0027] The converted starting product is at least partially dehydrated of bound water by heat treatment and / or reactive grinding. Bound water is also called crystal water. Bound water must be distinguished from unbound water, which can be considered as free H2O. Complete dehydration can be achieved at great expense. According to the invention, the moisture content of bound water must be reduced by at least 60%, preferably at least 80%, more preferably at least 90%.
[0028] In the heat treatment, the transformed starting product can be heated to a temperature of 180°C to 1000°C. Depending on the fineness of the starting product, only a few minutes of heating are sufficient. Heating is preferably at a temperature of 300°C to 800°C, more advantageously at a temperature of 500°C to 700°C. Alternatively or additionally, the transformed starting product can be subjected to reactive grinding to rearrange the crystal structure. In so-called reactive grinding, the crystal water can also be removed from the transformed starting product by rearranging the crystal structure. For this purpose, auxiliary materials such as quartz can be added to the grinding process.
[0029] In this step, the magnesium hydroxide (Mg(OH)2) present in the converted starting product is at least partially converted to magnesium oxide (MgO) and the magnesium silicate hydrates present (Mg3SiO5(OH)4, Mg3SiO4O 10(OH)2) is converted to at least partially dehydrated magnesium silicate hydrate, which can be simplified and represented as xMgO SiO2 yH2O. Dehydration refers to the reduction of water of crystallization or water in the transformed starting product. The underlying chemical process here can again be simplified as follows:
[0030] [ka]
[0031] Here, reaction (4) produces a nearly amorphous reaction product with a Mg to Si ratio of 1.5 to 2 and a bound water content of about 3%. The reaction product formed in reaction (5) has an even lower Mg to Si ratio. The variables a, b, c, x, y and z therefore also change. This depends in each case on the exact composition of the starting product and the processing parameters.
[0032] After dehydration, the moisture content of bound water in the converted and dehydrated starting product is preferably less than 10% by weight, more advantageously less than 5% by weight, even more preferably less than 3.5% by weight, particularly preferably less than 2.5% by weight.
[0033] Thus, the transformed and dehydrated starting product exists as a multiphase product. Other possible secondary phases include hematite, magnetite, enstatite, feldspar, pyroxene, quartz, and amorphous phases.
[0034] Once the converted starting products have been dehydrated, they are contacted with CO2. Here, the CO2 reacts with any magnesium oxide (MgO) present, any dehydrated magnesium silicate hydrates present (xMgO·SiO2·yH2O), and / or any magnesium hydroxides present (Mg(OH)2). The CO2 is primarily bound to the resulting magnesium carbonate (MgCO3) and / or magnesium carbonate hydrates (MgCO3-mH2O). The underlying chemical process can be represented in a simplified and generalized way as follows:
[0035] [ka]
[0036] where m, n, p, q, x, and y represent the corresponding variables. At least one of these can be zero. Also note that in equation (7), the dehydrated magnesium silicate hydrate appears only as xMgO·SiO2·yH2O because it is (incompletely) dehydrated. Equation (8) shows forsterite (Mg2SiO4), which may still be present. At this point, forsterite from the starting product may still be present. Also note that xMgO·SiO2·yH2O is very similar to forsterite and can be considered simply as amorphous forsterite.
[0037] The steps of addition of water and hydrothermal treatment can be omitted if a starting product is provided which already contains at least 20% by weight, preferably at least 40% by weight, more preferably at least 60% by weight, even more preferably at least 80% by weight of magnesium silicate hydrate, as is the case for example with serpentinite, which is a metamorphic rock formed by natural transformation, in particular weathering, of ultramafic rocks.
[0038] In accordance with the present invention, it has been recognised that a combination of hydrothermal treatment and removal of water of crystallisation from natural materials such as ultramafic rocks can produce an intermediate material suitable for highly binding CO2.
[0039] Olivine-rich rocks that can be used in the present invention include, for example, dunite, wehrlite, and habsburgite. These rocks tend to be lightly weathered. However, weathered rocks with similar chemical composition and high water content can also be used. Weathered rocks include, for example, serpentine.
[0040] In this way, large amounts of CO2 can be bound with relatively little energy input. For example, using the method of the present invention, about 1 tonne of forsterite can bind about 0.6 tonnes of CO2 within a few hours.
[0041] The hydrothermal treatment to convert the homogenized starting material into magnesium hydroxide and / or magnesium silicate hydrate is one of the most time-consuming process steps according to the invention. It is therefore advisable to carry out one or more treatments during the hydrothermal treatment to accelerate the ongoing reactions. For this purpose, various treatment methods are available, which can be carried out individually or in combination with one another. These are explained in more detail below. All, but only some, of the described treatment methods can be combined with one another.
[0042] One possibility is to continuously or discontinuously grind or disintegrate the homogenized starting product during the heat treatment or between heat treatments in the heat treatment device, in particular to grind very finely, to facilitate the conversion.
[0043] Continuous or discontinuous grinding can prevent or reduce the agglomeration or coalescence of the materials present during the hydrothermal treatment. This ensures a large enough surface area to carry out the above processes. Several options are available for the exact implementation:
[0044] On the one hand, it is possible to interrupt the hydrothermal treatment, remove the material from the heat treatment device, crush or disintegrate it, for example by grinding it, and return it to the heat treatment device again.
[0045] On the other hand, it is also possible to provide in the heat treatment device a corresponding grinding system which performs the grinding continuously or discontinuously during the hydrothermal treatment.
[0046] Another option is to operate the heat treatment device in particular continuously, and to discharge part of the material from the heat treatment device during the hydrothermal treatment, grind it and return it to the device again. This is particularly useful when the starting product is in suspension in the heat treatment device, or at least in a form that can be pumped. In this case, for example, a line can be provided that runs from the autoclave to a grinding device such as a mill and back to the autoclave again. This is an example of a heat treatment device in the sense of the present invention. In this case, it can be said to be an uninterrupted cyclic process.
[0047] Another option is to add nucleating agents, agents to increase the pH value, foreign ions, and / or other auxiliary materials to the starting product at the beginning of homogenization, before homogenization, during homogenization, immediately after homogenization, or in the heat treatment device in order to accelerate the process of reaction.
[0048] For example, brucite, lizardite, antigorite, pre-hydrated olivine-containing rocks, or mixtures of these materials can be added as nucleating agents, preferably in an amount of at least 2% by mass.
[0049] Substances that release NaOH, KOH, NaCl, KCl, Na2SO4, MgSO4, K2SO4, Na2CO3, Ca(OH)2, and / or K2CO3 upon addition can be added as agents to increase the pH value, thereby modifying the solution in which the reaction occurs, increasing the pH value in the solution and allowing the reaction to occur more quickly.
[0050] Other additives that accelerate the reaction include magnesite, hydromagnesite, nesquehonite, dolomite, SiO2, feldspar, pyroxene, and mixtures thereof, which may lead to the formation of new reaction products. Examples of foreign ions include aluminum, sulfates, and alkalis, which may also lead to the formation of new reaction products.
[0051] In order to increase the purity of the product resulting from CO2 sequestration, these auxiliary materials can be at least partially removed again after the hydrothermal treatment is completed.
[0052] In principle, the reaction process can also be carried out at elevated temperatures, in particular at temperatures of 150° C. or higher, preferably 200° C. or higher, more preferably 250° C. or higher.
[0053] A further method for accelerating the reaction is that the homogenized starting product is in suspension for hydrothermal treatment of the homogenized starting product in a heat treatment device, and the suspension is continuously or discontinuously stirred during the hydrothermal treatment, for example a stirrer can be provided here to ensure the movement of the suspension.
[0054] Alternatively or additionally, grinding can be carried out here as described above. Wet grinding is particularly suitable here, so that a part of the suspension can be transferred from the heat treatment device, wet-ground and returned to the heat treatment device again. However, wet grinding can also be carried out directly in the heat treatment device.
[0055] Alternatively, the homogenized starting product can be sonicated. Similar to milling, this separates any material formed on the starting product (such as magnesium hydroxide or magnesium silicate hydrate) from the rest of the material in the starting product, again providing a large enough surface area for the reaction to proceed quickly. Sonication can be done, for example, using an ultrasonic horn.
[0056] Depending on the desired further treatment and processing of the homogenized and converted starting product, it may be useful to carry out a dehydration step, i.e. drying, to remove unbound water prior to separation of the bound water, which is particularly indicated and useful when the hydrothermal treatment of the starting product was carried out in aqueous suspension.
[0057] The dried starting product is then fed to the dehydration step. The heat treatment proposed for this purpose is also called tempering or calcination. This can be carried out by means of a rotary furnace or a circulating fluidized bed of hot gases. With a fluidized bed, the dehydration takes place within a few seconds. Alternatively, the required energy can be supplied electrically, for example in a muffle furnace. In this case, a time of about 5 to 10 minutes is required. As a rule, open systems, for example with a flame, are preferred, since it is easier to remove the generated water vapor and the reaction is faster.
[0058] In principle, the bond with CO2 is formed simply by contacting the converted and dehydrated starting product with CO2 as present in air. However, the bond process can be enhanced and accelerated if the contact between the converted and dehydrated starting product and the CO2 in aqueous suspension is carried out, for example by bubbling in a CO2-containing gas, such as air. It has been demonstrated that this method step allows for more rapid bond with CO2 than treatment with normal ambient air alone in the absence of water.
[0059] The contact of the converted and dehydrated starting product with the CO2-containing gas can be carried out at partial pressures of at least 200 ppm, 400 ppm, 1000 ppm, 10,000 ppm, 100,000 ppm, 200,000 ppm, in particular already at room pressure (normal pressure) or in the range of up to 2 bar (corresponding to 2 million ppm). According to the invention, it is not necessary to apply high pressure in order to achieve a rapid and sufficient binding of CO2. However, the binding of CO2 is further accelerated by a higher partial pressure.
[0060] The fineness of the starting product was determined based on a BET surface area of 0.1 m 2To obtain a fineness of 0.1 g or finer, the starting product is preferably ground, in particular wet ground. The starting product is usually not available in a finer degree, even if it is already partially very fine due to natural weathering. This fineness can be easily increased by grinding. Wet grinding is also preferred here, since it is often more energy efficient than dry grinding. The starting product is then subjected to a hydrothermal treatment in contact with water, so that the advantages of wet grinding can already be exploited at this stage, especially since the ground material does not have to be dried.
[0061] The converted and dehydrated starting product can be used as a binder for concrete production before the CO2 is bound, e.g. as a full or partial replacement for cement. Here, the water / binder ratio is preferably in the range of 1:2 or less. This means that the ratio is 1:2.22, preferably 1:2.5, ideally 1:2.86 and even more preferably 1:3.33 or less. It has been found that the higher the ratio, i.e. the higher the water ratio, the longer the hardening and the lower the strength. The concrete produced in this way already binds the CO2 from the surrounding air at room temperature and at room temperature. In principle, the binding process can be further accelerated by heat or pressure treatment.
[0062] In another embodiment, the converted, dehydrated and CO2-bound starting product can be preferably solidified and supplied as aggregate or filler for the production of concrete and / or mortar. After the CO2 is bound, it can be dried again. However, this is not absolutely necessary, since during the CO2-binding, solids are already formed from the converted and dehydrated starting product or the strength of the hardened material is continuously increasing.
[0063] The material obtained is inert and suitable for further processing into concrete together with a hydraulic binder such as cement clinker. For this purpose, further grinding may be necessary. In principle, it is advantageous for the process of the method of the invention to have at least no cement clinker in the starting product. In particular, this means that the starting product contains no or very little (less than 0.1% by weight) alite and / or belite phases. Experience has shown that the presence of materials contained in cement clinker is undesirable, since they partially retard the reactions described here. However, the presence of small amounts of cement clinker is not problematic.
[0064] If necessary, other substances can be added to improve reactivity or to alter the properties of the hardened material. These substances include organic additives, especially superplasticizers, rock powders, especially limestone, dolomite, olivine, trass, glass powders, coal fly ash, and / or pozzolanic additives such as heat-activated clays.
[0065] The starting products provided by the present invention are usually not pure substances, and therefore contain a significant amount of impurities. However, it is advantageous if the molar ratio of Mg to Ca is at least 10:1 and / or the molar ratio of Si to Al is also at least 10:1. It has been found that the presence of calcium and aluminum relative to magnesium and silicon, respectively, slows down the reaction or even stops it completely. It is therefore not important to shift the corresponding molar ratios significantly in the direction of magnesium or silicon. Preferably, the molar ratio of Mg to Ca is at least 20:1 and / or the molar ratio of Si to Al is at least 20:1. EXAMPLES
[0066] The invention will now be explained in more detail on the basis of exemplary embodiments with reference to the drawings. FIG. 1 is a graph showing the hydration process of the product produced by the method of the present invention, and FIG. 2 is a graph showing the curve of CO2 concentration during the binding of CO2 by the product produced using the method of the present invention.
[0067] In order to verify the invention, inter alia, the tests detailed below have been carried out, in which, on the one hand, pure forsterite was used in the first tests and, on the other hand, natural olivine was used.
[0068] Pure Forsterite In the first study, pure forsterite (Mg2SiO4) was used, which was produced by calcining a mixture of magnesium carbonate hydroxide and amorphous SiO2 in a laboratory furnace. After calcination, the starting product was ground in a vibrating disc mill. The specific surface area after BET treatment was 1 m 2 / g.
[0069] A mixture of forsterite and 1 molar NaOH solution in a ratio of 1:2.2 was then prepared and treated in an autoclave at a temperature of 200 °C. During this time, the reaction was interrupted and the material was dried and crushed. After a treatment period of 4 weeks, the treated and washed material was examined using X-ray phase analysis and no forsterite was detected. The loss on ignition after the autoclaving was completed was 19.3% by mass.
[0070] 3.0 g of the dried and crushed material was placed in a platinum crucible and fired in a muffle furnace at temperatures of 450°C, 600°C, and 750°C for 1 h. The ignition losses of the samples were 13.5% by mass (450°C), 2.8% by mass (600°C), and 0.52% by mass (750°C), respectively.
[0071] isolation This material was used to sequester CO2. For this purpose, 1 g of the sample calcined at 600 °C was placed in a glass beaker with 50 g of water and the suspension was stirred continuously. At the same time, gaseous CO2 (100% concentration) was introduced into the suspension. After 6 hours, the suspension was filtered and separated, and after drying the solid was analyzed by X-ray diffraction and29 The compound was analyzed by Si MAS NMR.
[0072] X-ray phase analysis showed that nesquehonite (MgCO3·3H2O) was the only crystalline reaction product. 29 Using Si MAS NMR, it has been shown that all of the silicon exists as amorphous SiO2. Thus, the following reaction is demonstrated, where only the initial and final states are shown, omitting the intermediate steps:
[0073] [ka]
[0074] Thus, carbon dioxide can be sequestered using the methods of the present invention.
[0075] Binder (binding material) The reactivity of the materials before isolation as binders was investigated by measuring their water binding after 7 days of hydration. For this purpose, materials calcined at different temperatures were ground on a railing, mixed with water in a water to binder ratio of 0.50 (1:2) and stored in a closed container at 22 °C for 7 days. The hydration of the samples was then stopped by drying at 60 °C and the loss on ignition was measured by thermal analysis. The ignition losses were 20.5% (450°C), 25.3% (600°C), and 7.1% (750°C), respectively. Thus, all three binders contain water of hydration and water of bond.
[0076] The hydration process of the sample calcined at 600 °C was analyzed by calorimetry (DCA) at 25 °C. The process showed a very fast reaction, with the main hydration stage maximizing after about 2 h and the reaction being complete in less than 24 h. A total heat of about 450 J / g was released, as shown in Figure 1.
[0077] As a result, the binder reacts faster than most conventional cements. 29Examination of the hydrated and dried samples after DCA analysis using Si MAS NMR spectroscopy showed that all the silicon was present as magnesium silicate hydrate.
[0078] Natural olivine In the following study, natural olivine from a Norwegian source was used. Chemical analysis revealed the following composition: 41.9% SiO2, 49.9% MgO, 6.9% Fe2O3, 0.6% Al2O3, 0.1% CaO, and 0.5% loss on ignition.
[0079] The material was milled at 7300 cm 2 The material was ground to a fineness of 100 / g Blaine and mixed with 1M NaOH solution in a 1:2 ratio. The material was autoclaved at 200°C for 22 days, with one interruption during this time to grind the material. After autoclaving, the intermediate product was dried, crushed and analyzed for loss on ignition (16.3% by weight).
[0080] isolation Carbon dioxide sequestration was then investigated. For this purpose, 10 g of intermediate product calcined at 600 °C was used. This intermediate product was ground after heat treatment for 4 minutes at 700 revolutions per minute in a disk vibratory mill with the addition of triethanolamine. The olivine pretreated according to the invention was added to 1 liter of water and stirred continuously. Normal ambient air was blown into this suspension using a simple aquarium pump. The CO2 concentration of the ambient air was about 400 ppm. In a closed room, the CO2 concentration is usually somewhat higher, usually between 500 and 600 ppm.
[0081] During the experiment, the CO2 concentration was measured in the air rising from the suspension. During the experiment, the concentration dropped continuously and rapidly to about 200 ppm. It was possible to remove carbon dioxide from the air introduced over a period of several days. Thus, the material is able to react with CO2 in the air and permanently bind it in the form of magnesium carbonate. The results are shown in Figure 2.
[0082] Binder (binding material) Individual batches of the intermediate product were calcined at different temperatures and hydrated for 7 days at 22° C. to investigate water binding. The loss on ignition before hydration (6.8% by mass after 550° C., 3.1% by mass after 600° C., 2.2% by mass after 650° C., 1.7% by mass after 700° C.) was lower than after reacting with water and drying at 60° C. (20.1% by mass after 550° C., 23.7% by mass after 600° C., 24.7% by mass after 650° C., 22.8% by mass after 700° C.).
[0083] As a result, natural materials such as olivine may also be used to manufacture binders, and hydration after the pretreatment mentioned above may be demonstrated.
[0084] Thus, it has been shown that the method of the present invention can be used to efficiently bind CO2. Furthermore, a binder for concrete production can be produced as a by-product, which can also be used for CO2 sequestration.
Claims
1. a) providing a starting product comprising at least 20% by weight of one or more of the following components: Ultramafic rocks, especially dunite, - Weathering products of ultramafic rocks, especially serpentinite, - Olivine, ・Industrial waste, (Each has an MgO concentration of at least 10% by mass and 2 / g or more), b) homogenizing the starting product; c) subjecting the homogenized starting product to hydrothermal treatment in a heat treatment device at a temperature of 100° C. or higher for at least 24 hours; d) adding water to the homogenized starting product by adding water immediately before, after, and / or simultaneously with the homogenization of step b), mixing the water with the starting product, and / or introducing steam into the heat treatment device, wherein after step c), the starting product is heated to a temperature of 1000° C. 2 Magnesium hydroxide Mg(OH) at least partially in the presence of O 2 and / or converted to magnesium silicate hydrate, e) at least partially dehydrating the bound water from the converted starting product by thermal treatment and / or reactive grinding; f) reacting the converted and dehydrated starting product with CO 2 and contacting the CO 2 1. A method for isolating a In step e), during the heat treatment, the transformed starting product is treated at a temperature of 180° C. to 1000° C., and during the reactive grinding, a rearrangement of the crystal structure of the transformed starting product occurs; After step e), the magnesium hydroxide present in the converted and dehydrated starting product is at least partially dehydrated to magnesium oxide and the magnesium silicate hydrates present are at least partially dehydrated and converted to dehydrated magnesium silicate hydrates, In step f), the CO 2 reacts with the magnesium oxide, the dehydrated magnesium silicate hydrate and / or the magnesium hydroxide, 2 is bound to the resulting magnesium carbonate and / or magnesium carbonate hydrate, The steps c) and d) can be omitted if the starting product, e.g. the serpentine, is prepared which already contains at least 20% by weight of the magnesium silicate hydrate. 2 How to isolate.
2. 2. The method of claim 1, wherein for at least partial conversion of the starting product in step c), one or more treatments are carried out to promote reactions occurring during the hydrothermal treatment.
3. 3. The method according to claim 1 or 2, wherein the homogenized starting product is continuously or discontinuously ground, in particular finely ground, during the hydrothermal treatment or between multiple hydrothermal treatments in the heat treatment device in step c) to facilitate the conversion.
4. 4. The method according to claim 1, wherein nucleating agents, agents for increasing the pH value, foreign ions and / or auxiliary substances are added to the starting product in steps a), b), c) and / or d).
5. 5. The method according to claim 4, wherein after step c), the auxiliary material is at least partially removed again.
6. 6. The method according to claim 1 , wherein for subjecting the homogenized starting product to the hydrothermal treatment in the heat treatment device, the homogenized starting product is present in a suspension which is continuously and / or discontinuously stirred during the hydrothermal treatment.
7. 7. The method according to claim 1, wherein in step c) an ultrasonic treatment of the homogenized starting product is performed.
8. The converted and dehydrated starting product and the CO 2 Contact with CO 2 8. The process according to claim 1, which is carried out in aqueous suspension by bubbling with a contained gas.
9. The converted and dehydrated starting product and the CO 2 9. The process according to claim 1, wherein the contact with the gas containing is carried out at a partial pressure of at least 200 ppm, in particular at atmospheric pressure.
10. 10. The method according to claim 1, wherein the converted starting product is dried prior to step e) to remove unbound water.
11. To the starting product, 0.1 ml 2 11. The method according to claim 1, wherein the starting product is subjected to grinding, in particular wet grinding, to give it a fineness corresponding to a BET surface area of at least 1000 nm / g.
12. After step f), the CO 2 12. The method according to any one of claims 1 to 11, wherein the combined starting product is solidified and serves as aggregate or filler for the production of concrete and / or mortar.
13. 13. The method according to claim 1, wherein after step e) the converted and dewatered starting product is used as a binder for the production of concrete, wherein the water:binder ratio is not more than 1:
2.
14. 14. The method according to any one of claims 1 to 13, wherein the starting product has a molar ratio of Mg to Ca of 10:1 or more and / or a molar ratio of Si to Al of 10:1 or more.
Citation Information
Patent Citations
Method for utilizing carbon dioxide
JP2006076825A
Integrated Chemical Method
JP2010510161A
Method and system of activation of mineral silicate minerals
US20170029284A1
Integrated chemical process
WO2008061305A1